PROFILE OF THE BRAZILIAN RESEARCHES ON CAFFEINE AND PHYSICAL EXERCISE (Fiep Bulletin - online, 2011)
Introduction: The knowledge of the direction of scientific production of an area is fundamental to improving the quality of research for the advancement of science and especially for diagnosing the impact of this production in our society. The search for explanations of the paths taken by research on caffeine highlights their achievements, gaps and calls attention to new alternatives for investigations. Objective: To identify the profile of research in Brazil on caffeine and physical exercise. Methodology: This study was conducted through literature search, critical-epistemological in nature, with quantitative and qualitative analysis, where it searched the articles produced in Brazil linking caffeine to physical exercise, indexed in LILACS and SCIELO. Results: 31 articles were found in the LILACS database and eight on database SCIELO that studied the effect of caffeine on aerobic exercises (11 articles) and anaerobic exercises (6 articles), and caffeine doping (6 articles), caffeine and perceived exertion (5 articles), concentration of caffeine in ergogenic beverages (3 articles) and other goals (8 articles), which identified the Brazilian journal of sports medicine as the journal that publishes more this subject (9 articles). The removal of caffeine from the doping list of World Anti-Doping Agency has increased the amount of researches in the area. The main control variables of the studies analyzed were the intensity of exercise, caffeine dosage and duration of supply of the product before exercise. Conclusion: the quantity of Brazilian researches on caffeine and exercise are insufficient, performed with small and restricted samples where the variables need greater control, as the temperature of ingested substances, environmental aspects and the homogeneity of the sample.
Keywords: Caffeine; Ergogenic; Performance; Doping